Darned if you do eaudiobook - Ferris, Monica (Needlecraft Mystery, 2015)
After a tree falls on Tom Riordan's house, landing him in the hospital, the police discover a mountain of junk piled high in his home. Locals in Excelsior, Minnesota - including Betsy and her Crewel World Monday Bunch - offer to help with the cleanup while Tom recuperates. But when Tom is found murdered in his hospital bed, the sole heir to his property - his cousin Valentina - becomes the number one suspect. Betsy believes there's more to the case than meets the eye, but finding clues to the killer's identity in the clutter Tom left behind will be like looking for a needle in a haystack...